The tender detail ornament and sentimentality in the architecture of Louis H. Sullivan and Frank Lloyd Wright - Snyder, Daniel E. (London : Bloomsbury Visual Arts, 2020)
"The Tender Detail tells a story about the repression of sentimentality through architectural ornament. The protagonists are Louis H. Sullivan and Frank Lloyd Wright, two of the most important architects and designers of ornament in American history. Exploring how both men worked to solve the problem of late nineteenth-century ornamentation, the book interweaves close readings of their buildings and writings with wide ranging discussions across the fields of architecture, sexuality, gender, and philosophy. It suggests that their solutions, while widely different, were both intimately rooted in the tender emotions of sentimentality. Viewing ornament in this way reveals much, not only about Sullivan and Wright's artistic intentions, but also about the role of affect, the value of beauty, and the agency and ontology of objects. Illuminated by personal stories from their respective autobiographies, which add a level of human interest unusual in an academic work, The Tender Detail is a readable, scholarly study which sheds fresh light on Sullivan and Wright's relationship, their work, and on the nature of ornament itself."--
List of Illustrations Acknowledgements Preface -- 1 -- Introduction: Frank Lloyd Wright, ?sentimentalizing over the dead? -- Part One: Louis H. Sullivan -- 2 -- ?the plastic decorations are distinctly architectural in conception? -- 3 -- ?that object he became? -- 4 -- ?feminity? -- Part Two: Frank Lloyd Wright -- 5 -- ?no damned sentimentality either? -- 6 -- ?Integral Ornament at Last? -- 7 -- ?'like a man'? -- Part Three: Louis H. Sullivan and Frank Lloyd Wright 8 -- ?that supreme erotic adventure of the mind? -- 9 -- Ornament ?purely as such? -- 10 -- Epilogue: ?when we are dead? -- Bibliography Index
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Sullivan, Louis H., -- 1856-1924 -- Criticism and interpretation; Wright, Frank Lloyd, -- 1867-1959 -- Criticism and interpretation; Sullivan, Louis H., -- 1856-1924; Wright, Frank Lloyd, -- 1867-1959; Decoration and ornament, Architectural; Sentimentalism; Décoration et ornement architecturaux; Sentimentalisme; architectural ornament; History of architecture; Decoration and ornament, Architectural; Sentimentalism; Informational works; Criticism, interpretation, etc; Informational works; Documents d'information.